2011
DOI: 10.1002/cjoc.201180272
|View full text |Cite
|
Sign up to set email alerts
|

Isosteviol‐amino Acid Conjugates as Highly Efficient Organocatalysts for the Asymmetric One‐pot Three‐component Mannich Reactions

Abstract: Isosteviol-amino acid conjugates were synthesized and used as chiral catalysts for the asymmetric three-component Mannich reaction with hydroxyacetone as donor molecule. Good yields (up to 98%) and excellent stereoselectivities (up to 97∶3 dr and 99% ee) were achieved in a short reaction time. In addition, syn-or anti-configurations of α-hydroxy-β-amino carbonyl compounds were obtained as main products with different chiral catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Isosteviol-amino acid conjugates were synthesized and used as chiral catalysts for the asymmetric three-component Mannich reaction with hydroxy acetone as a donor molecule. Good yields (up to 98%) and excellent stereoselectivities (up to 97:3 dr and 99% ee) were achieved in a short reaction time [ 179 ].…”
Section: Other Miscellaneous Usesmentioning
confidence: 99%
“…Isosteviol-amino acid conjugates were synthesized and used as chiral catalysts for the asymmetric three-component Mannich reaction with hydroxy acetone as a donor molecule. Good yields (up to 98%) and excellent stereoselectivities (up to 97:3 dr and 99% ee) were achieved in a short reaction time [ 179 ].…”
Section: Other Miscellaneous Usesmentioning
confidence: 99%
“…Nevertheless, the skeleton structures to construct thiourea catalysts are very limited, and there is still great demand for novel bifunctional thiourea catalysts for this purpose. Recently, we found that, similar to the cinchona alkaloids, the incorporation of a chiral diterpene moiety (isosteviol) into the thiourea catalysts led to impressive results in asymmetric reactions . Inspired by the excellent chiral structural skeleton of isosteviol, we designed and synthesized a new class of primary amine‐thiourea bifunctional catalysts 3a and 3b .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we found that, similar to the cinchona alkaloids, the incorporation of a chiral diterpene moiety (isosteviol) into the thiourea catalysts led to impressive results in asymmetric reactions. [31][32][33][34][35][36][37] Inspired by the excellent chiral structural skeleton of isosteviol, we designed and synthesized a new class of primary amine-thiourea bifunctional catalysts 3a and 3b. With these novel catalysts in hand, the effects of the thiourea catalysts were investigated.…”
Section: Introductionmentioning
confidence: 99%